Influence of Black Soldier Fly Frass Fertilizer on Growth and Southern Blight Disease Development in Okra (Abelmoschus Esculentus (L.) Moench) - Oladimeji, Ahmed; OJUMOOLA, Olusegun Adebayo; Lateef, Adebola Azeez; ADEYEMI, Evelyn Blessing; ABDULLAH, Aminat Jummai (Jordan Journal of Agricultural Sciences, 2025)
Black Soldier fly (Hermetia illucens) larval (BSFL) frass is gradually becoming a source of organic fertilizer in cropping systems because of its role in improving crop growth and development as well as suppressing the growth of fungal pathogens. This study evaluated the effect of Black Soldier Fly Frass Fertilizer (BSFFF) on the growth of Okra (Abelmoschus esculentus) plant and development of southern blight disease during its growth. The BSFFF was applied at the rate of 10g, 15g, and 20g per 3kg of heat pasteurized soil in (5 litre capacity and 20 cm-diameter at the top and 15 cm height) plastic pots. No BSFFF application served as control while NPK 20:10:10 was applied at the rate of 30 kg ha-1 to serve as a check. Results showed no significant difference (p=0.05) in the growth parameters on BSFFF-treated okra plants regardless of level of application. From the second to fifth weeks after sowing (WAS), the growth parameters of okra plants treated with BSFFF at all levels were significantly different (p = 0.00001) from those of untreated and NPK-treated plants. Plant heights in the first and sixth WAS ranged from 15.95±0.53 to 37.65±2.63 cm, respectively. From the second to fifth WAS, stem girth of okra plants treated with BSFFF at all levels was significantly wider (p = 0.00001) than that of untreated and NPK-treated plants. At two WAS, the number of leaves (6.56 ± 0.24) on okra BSFFF20 treated plants was significantly (p = 0.0098) more than that of control plants (5.20± 0.13). However, from 3 WAS, there was a steady reduction in the number of leaves on okra plants irrespective of the treatment received, probably due to the onset of disease symptoms. At 4 WAS, the number of leaves on BSFFF20 (5.67± 0.33) treated plants was again significantly more (p = 0.0003) than that of untreated plants despite the moderate incidence of disease symptoms on plants. The findings in this study demonstrate that integration of BSFFF into the okra cropping system would improve the growth and development of the okra plant and boost its tolerance to southern blight disease.